Clinical thinking as the important stage of future doctors preparation. - Yu. V. Sukhin; Yu. Ty. Pavlychko; V. P. Topor (Kazimierz Wielki University, 2016)
In the article the main stages of the formation of clinical thinking in future doctors from the point of view of industry standards "Educational and professional training program of a specialist" and "Educational and qualifying characteristics of a specialist" are considered.